2020
DOI: 10.2478/rrlm-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

The role of neutrophil to lymphocyte ratio in patients with pTa non-muscle invasive bladder cancer

Abstract: Introduction:The peritumoral inflammatory reaction has a substantial importance in the oncologic outcome of bladder cancer (BC). One biomarker proven to be practical and accessible is the NLR (neutrophil-to-lymphocyte ratio) for high risk non-muscle invasive bladder cancer (NMIBC). The aim of the study was to investigate the role of NLR as a prognostic biomarker for disease recurrence, progression and survival of p Ta (pathological assesment of the primary tumor) NMIBC. Material and Methods: In our retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Moreover, some studies have shown that the high value of NLR is associated with a higher recurrence rate and lower overall survival. Our data are in agreement with those published in the literature proving a positive relationship between the increased ratio of neutrophils and lymphocytes in people diagnosed with non-muscle invasive bladder cancer and increased mortality rate, p = 0.003 [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, some studies have shown that the high value of NLR is associated with a higher recurrence rate and lower overall survival. Our data are in agreement with those published in the literature proving a positive relationship between the increased ratio of neutrophils and lymphocytes in people diagnosed with non-muscle invasive bladder cancer and increased mortality rate, p = 0.003 [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 92%
“…An increased value of preoperative NLR is related to poorer prognosis. Moreover, some studies have shown that a high value for NLR is associated with a higher recurrence rate and lower overall survival [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The IMPROVE score is a validated tool for assessing patients for the three-month risk of thrombosis, although the IMPROVE Bleeding score is lacking researchers' attention [7,8]. The prognostic role of NLR in tumor progression and disease recurrence has been highlighted in previous studies, but to the best of our knowledge in cancer patients, few have investigated the association of non-specific pro-inflammatory markers derived from CBC and bleeding risk [9,10]. Therefore, we aimed to evaluate the relationship of NLR, LMR, and the risk of thrombosis by using the IMPROVE score as well as the risk of bleeding using the IMPROVE Bleeding Risk Assessment Score in patients with non-muscle-invasive bladder tumors.…”
Section: Introductionmentioning
confidence: 99%